The role of power in wellness, oppression, and liberation: The promise of psychopolitical validity - Prilleltensky, Issac (John Wiley & Sons Inc, 2008)
The power to promote wellness, resist oppression, and foster liberation is grounded in psychological and political dynamics. Hitherto, these two sources of power have been treated in isolation, both for descriptive and prescriptive purposes. As a result, we lack an integrative theory that explains the role of power in promoting human welfare and preventing suffering, and we lack a framework for combining psychological and political power for the purpose of social change. In this article, the author puts forth a psychopolitical conceptualization of power, wellness, oppression, and liberation. Furthermore, he introduces the concept of psychopolitical validity, which is designed to help community psychologists to put power issues at the forefront of research and action. Two types of psychopolitical validity are introduced: type I - epistemic, and type II - transformative. Whereas the former demands that psychological and political power be incorporated into community psychology studies; the latter requires that interventions move beyond ameliorative efforts and towards structural change. © 2008 Wiley Periodicals, Inc.